Two new sympatric species of the pirate spider genus Ero C.L. Koch, 1836 from the cloud forest of Saint Helena Island, South Atlantic Ocean (Araneae: Mimetidae) - Danniella Sherwood; Arnaud Henrard; Martina Peters; Benjamin W. Price; Andie C. Hall; Oliver W. White; Virginie Grignet; Vicky Wilkins (European Journal of Taxonomy, 2024)
A remarkable morphologically and genetically distinct species of the genus Ero C.L. Koch, 1836 is described based on both sexes from the cloud forest of the island of Saint Helena: Ero lizae sp. nov. Another new species, Ero natashae sp. nov., is also described on the basis of morphological differences in the male and female genitalia. Both species were initially reported a single species, Ero aphana (Walckenaer, 1802), from the island by Unzicker (1977).